The Overview of Sanitation Hygiene of Food Stalls in the Working Area of the Bara-Baraya Health Centre, Makassar, Indonesia - Annisa Y Febrianti; Najamuddin Najamuddin; Rosdianah Rahim; Purnamaniswaty Yunus; Rini Fitriani; Darmawansyih Darmawansyih (CV. Global Health Publication, 2026)
Background: Food security remains a public health concern in Indonesia, particularly in informal food sectors such as food stalls, where inadequate knowledge and practices related to hygiene and sanitation may increase the risk of foodborne diseases. Poor sanitation conditions in food management sites can negatively affect community health and food safety. Aim: This study aimed to describe the hygiene and sanitation conditions of food stalls in the working area of the Bara-Baraya Health Centre in 2025. Method: This study employed a descriptive survey method conducted in October 2025. The research involved five food stalls that voluntarily participated in the study. Data were collected through direct observation using an environmental health inspection form based on the Regulation of the Minister of Health of the Republic of Indonesia Number 43 of 2014 concerning Sanitation Hygiene of Food Management Sites. Results: The results showed that only one food stall (20%) met the required hygiene and sanitation standards, while four food stalls (80%) did not meet the requirements. The most common deficiencies were related to kitchen cleanliness, separation of raw and cooked food, availability of soap at handwashing facilities, and inappropriate food handler behaviour. Conclusion: The implementation of hygiene and sanitation practices in most food stalls within the Bara-Baraya Health Centre area is still inadequate. Strengthened supervision, continuous coaching, and education for food handlers are needed to improve food safety and protect public health.